PENANAMAN MODAL ASING DAN PERTUMBUHAN INDUSTRI DI ASEAN(6), CHINA, INDIA, DAN KOREA SELATAN 1999-20041 - Kusumastuti, Sri Yani (Journal of Indonesian Economy and Business, 2008)
The objective of this study is to shed light on the determinants of foreign directÂ investment (FDI) in Asian developing countries and their impact on industrial growth. InÂ order to undertake it, we perform an econometric model based in panel data analysis for 9Â countries (such as ASEAN 6, China, India, and Korea) for the 1999-2004 periods. Weestimate the simultaneous equation using panel data estimation with fixed effect andÂ random effect. Among the major conclusions we have that the FDI is determined byÂ country risk and variables related to macroeconomic indicators like inflation, risk,Â economyâs degree of openness and average rate of economic growth, average rate ofworld economic growth, and level of education. The results also show that the FDI hasÂ been closely associated with corruption perception index and performance of FDI in theÂ past. However the other variables, such as the global competitive index and rank ofÂ investment performance and potential have no more influential on FDI inflows. Finally, weÂ have that the growth of industrial sector is positively related to the FDI inflows.Keywords: foreign direct investment, panel data, simultaneous equation, ASEAN